The possible use of horizontal propulsion in imitation ski jumps - Ettema, G.; Hooiveld, J.; Braten, S.; Bobbert, M. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: There are several differences between imitation jumps and actual jumps in ski jumping, such as equipment, speed, air resistance, and ground friction. No or little Information is available on the effect of having full friction between jumper and surface in imitation jumps on the coordination pattern. This is important for the evaluation of imitations jumps with regard to technique training for actual ski jumping. In actual ski jumping, the athlete has no option to use horizontal ground forces for propulsion because the friction always acts against the movement direction. In imitation jumps on a full friction surface, jumpers have that possibility, regardless the instruction on jumping technique. We examined this issue in imitation jumps that ski jumpers regularly perform during technique training.